Enhancing the implementation of smart ports through data governance and human resource development: Case Study of Tanjung Perak Port, Surabaya, Indonesia (BIS Humanities and Social Science, 2026)
The transformation of conventional ports into smart ports through the application of the Internet of Things (IoT) faces two main challenges, namely effective data governance and human resource capacity building. This study examines the contribution of data governance and technology integration to the operational efficiency of smart ports, identifies implementation barriers, evaluates their impact on port competitiveness through reducing dwelling time, and develops a progressive policy model that integrates regulatory innovation with human resource development. This study uses a mixed-methods sequential explanatory design, which combines quantitative, qualitative, and regulatory analysis at Tanjung Perak Port, Surabaya. Quantitative data from 48 port workers were analyzed using descriptive statistics. Qualitative data from stakeholder interviews and field observations were analyzed using thematic content analysis. The regulatory analysis examines Indonesia's smart port legal framework through a document review and compares it with Dutch and Singapore regulations to identify harmonization gaps and compliance challenges with international conventions. The implementation of the Terminal Booking System (TBS) has succeeded in reducing dwelling time from four days to two to three days (an increase of more than 25%), with 95.8% of workers reporting reduced workload. AI and data analytics skills. The regulatory analysis reveals that although Indonesia already has adequate smart port regulations, the challenge of harmonizing between existing legal frameworks and international conventions is still ongoing. This research proposes a tripartite policy architecture that integrates regulatory sandbox mechanisms adapted from the financial technology sector, immediate advanced technology training programs, and standardized certifications to bridge the workforce capacity gap.